Human Transferrin Detection Through a Mass-Sensitive Biosensor Utilizing ZnO Thin-Films via Atomic Layer Deposition - Alev, Onur; Kilic, Alp; Coban, Muzeyyen; Tokyay, Begum K.; Buyukkose, Serkan; Ozturk, Selma; Ozturk, Zafer Z. (IEEE-Inst Electrical Electronics Engineers Inc, 2024)
In this letter, we present the first example of a zinc oxide (ZnO) thin film grown by atomic layer deposition method (ALD) on a quartz crystal microbalance (QCM) for the detection of human transferrin (hTF) molecule. Morphological, structural, and optical properties of ZnO thin film were investigated by scanning electron microscopy, atomic force microscopy, X-ray photoelectron spectroscopy, X-ray diffraction spectroscopy, ultraviolet-visible spectroscopy, and photoluminescence. For biosensor measurements, ZnO/QCM sensors were modified with antitransferrin to obtain selectivity against hTF. Mass-sensitive biosensor tests were carried out using two different measurement methods: dip-dry and flow-cell. It was observed that antitransferrin immobilized ZnO/QCM sensor detected hTF molecule in the range of 100-1000 ng. Moreover, the sensors exhibited better performance in the dip-dry method than the flow-cell method. ZnO-coated QCM exhibited good mass-sensitive performance, which make it a suitable sensor platform for biosensor applications.
Keywords: Mass sensors; atomic layer deposition (ALD); biosensor; human transferrin (hTF); quartz crystal microbalance (QCM); zinc oxide (ZnO)